La problématique des « droits sur le carbone » dans REDD+ - Alain Karsenty; Aurélie Vogel; Driss Ezzine de Blas; Judicaël Fétiveau (VertigO)
Carbon credits issued from the Clean Development Mechanism forest projects generally belong to project investors. Nevertheless, such an issue remains highly conflicting when dealing with REDD+. Voices arise against the risk of investors capturing much of the expected benefits from REDD+ projects. In the present paper we argue that this may not be the right issue to be tackled. Although both the REDD+ governance architecture and its funding mechanisms are still to be decided, we argue that this risk may be valid only in the case of carbon credits issued from projects. We also argue that this risk will also depend on the economic model behind REDD+ projects. If projects adopt an approach of being paid for the provision of environmental services, paying legal or traditional forest owners for conserving forest carbon stocks makes sense. This approach can be described as a “conservation rent”, and has been highly criticized by economists for undermining effectiveness. Another approach would be to get paid for an “active contribution” to a particular environmental objective. In this case, we argue that a specific right arises from this activity, different from the rights over the resource. Here, carbon property rights can be invoked to share the carbon rent, if any. In the end, to clarify the debate around carbon rights amounts to distinguish benefits from rent.